Desenvolvimento de Testes Imunoquímicos e Moleculares para o Diagnóstico da Leptospirose - Fernandes, Cláudia Pinho Hartleben (2008)
Leptospirosis is a zoonotic disease that occurs all over the world and is caused by pathogenic bacteria of the genus Leptospira. Clinical manifestations of leptospirosis are similar to other febrile illnesses and this fact frequently retards beginning of antibiotic therapy. Thus, early and accurate diagnosis is a prerequisite for proper treatment of leptospirosis. Pathogenic serovars of Leptospira have a wide antigenic diversity attributed mainly to the lipopolysacharide present in the outer membrane. In contrast, antigens conserved among pathogenic serovars are mainly represented by outer membrane proteins. Surface exposure of a major and highly conserved outer membrane lipoprotein (LipL32) was recently demonstrated on pathogenic Leptospira. LipL32 on its recombinant form (rLipL32) was used to immunize BALB/c mice to develop murine monoclonal antibodies (mAbs). Three mAbs against rLipL32 were produced, isotyped and evaluated for further use in diagnostic tests of leptospirosis using different approaches. The mAbs were conjugated to peroxidase and evaluated in a native protein ELISA with intact and heat-treated leptospiral cells, conjugated to fluorescein isothiocyanate (FITC) for direct immunofluorescence with intact and methanol fixed cells and were used for LipL32 immunoprecipitation from leptospiral cells. rLipL32 mAbs conjugated to peroxidase or used as primary antibody bounded to intact and heat-treated cells in ELISA, proving that they could be used in enzyme immunoassays for detection of the native protein. On immunofluorescence assay, mAbs labeled bacterial cells either intact or methanol fixed. Two mAbs were able to immunoprecipitate the native protein from live and motile leptospiral cells and, adsorbed onto magnetic beads, captured intact bacteria from artificially contaminated human sera for detection by PCR amplification. One mAb was utilized for the development of an immunoseparation assay coupled to PCR test (IMS/PCR) for diagnosis of leptospirosis. The antibody adsorved onto magnetic beads captured leptospires from urine and human sera artificially contaminated for further amplification of the lipL32 gene by PCR. To ensure PCR accuracy, an internal amplification control (IAC) was constructed using as amplification targets sequences of standardized primers specific for pathogenic Leptospira and for a not-related DNA sequence. The IMS/PCR IAC method developed was able to detect 102 cells per mL of sera or urine, corresponding to approximately 25 genomic copies per reaction. These results suggest that the association of LipL32-based immunochemical and molecular techniques could yield a novel method for the diagnosis of leptospirosis. Moreover, immunomagnetic separation with mAbs against LipL32 can be used previous to amplification of other targets in the Leptospira genome by PCR.